10th International Conference on Nuclear Engineering, Volume 3 2002
DOI: 10.1115/icone10-22255
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fluid Mixing for Evaluation of Thermal Striping in T-Pipe Junction

Abstract: A water experiment is performed to investigate thermal striping phenomena in a T-pipe junction which is a typical geometry of fluid mixing. The flow velocity ratio and temperature difference were experimental parameters. The jet form was classified into four patterns; (1) impinging jet, (2) deflecting jet, (3) re-attachment jet and (4) wall jet according to the inflow condition. The parameter experiments showed that the jet form could be predicted by a momentum ratio between the two pipes. The thermochromic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…From the flow visualization test, the flow patterns of jet exiting from the branch pipe could be classified into (1)wall jet, (2)deflecting jet, and (3)impinging jet according to the inflow condition. It was confirmed that each jet form could be predicted by momentum ratio of main to branch flows (Igarashi, 2002).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…From the flow visualization test, the flow patterns of jet exiting from the branch pipe could be classified into (1)wall jet, (2)deflecting jet, and (3)impinging jet according to the inflow condition. It was confirmed that each jet form could be predicted by momentum ratio of main to branch flows (Igarashi, 2002).…”
Section: Introductionsupporting
confidence: 57%
“…The velocity measurement was mainly carried out in the wall jet case and the temperature difference was zero (isothermal condition). The influence of buoyancy force was negligible under the velocity conditions of over 0.1m/s in the main pipe (Igarashi, 2002). The measurements were carried out under steady state condition; the flow rates and temperatures at the inlets of main and branch pipes were kept constant.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…in pipelines in power plants. Recent studies using advanced scale-resolving methods such as LES and DES have shown promising results ( [3], [5], [6], [7], [12], [15] and [17]). However, detailed validation of the tools and methods is still required in order to determine their range of validity and their expected accuracy.…”
Section: Vattenfall Testcase -Thermal Striping In Thermal Fluid Mixingmentioning
confidence: 99%
“…Thus, thermal striping may be an issue for the CIP and has been recognized as one of the most important issues in design and safety of the JSFR. [2][3][4] In JAEA, experiments [4][5][6][7][8] and numerical analyses 3,[9][10][11] have been performed in order to evaluate thermal striping phenomena and to establish an evaluation ÓAtomic Energy Society of Japan method for the high-cycle thermal fatigue in JSFR. As for the evaluation method, Kasahara et al 12) proposed a thermal fatigue evaluation method based on power spectrum density (PSD) of temperature fluctuation in a fluid and a frequency transfer function from the fluid temperature fluctuation to thermal stress in the structure.…”
Section: Introductionmentioning
confidence: 99%